Syntheses and QSAR Studies of Benzylimidazole Derivatives and Benzylcarbazole as Potential Aromatase Inhibitors - Dai, Y.; Xiao, Y.; Wang, Q.; Wei, S.; Zhang, X.; Ma, Z.; Zheng, H.; Hou, M.; Zhang, T. (Asian Journal of Chemistry, 2014)
In this study, in order to explore new structures and chemical entities as aromatase inhibitors, benzylcarbazole, 12 benzylimidazole derivatives with different substituents on both phenyl and imidazole rings were synthesized and their aromatase inhibitory were evaluated with fluorescent substrate detection method. The results showed that the compounds with carboxyl and ester groups in phenyl ring show better inhibitory activity. The introduction of alkyl groups in imidazole may improve the aromatase inhibitory activity. Most of the compounds were more potent than aminoglutethimide and tamoxifen. 2-[2-{(2-ethyl-4-methyl-1H-imidazol-1-yl)methyl}phenyl]acetic acid and benzylcarbazole have the highest bioactivities with IC50 values of 6.19 μM and 2.72 μM respectively. A meaningful QSAR model with LOF = 0.00359, R2 = 0.9914, Adj-R2 = 0.9853, R2cv = 0.9639, F = 161.8, was constructed with genetic functional algorithm using discovery studio 2.1 package.